Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.chemosphere.2017.03.110
|View full text |Cite
|
Sign up to set email alerts
|

On the kinetics of organic pollutant degradation with Co2+/peroxymonosulfate process: When ammonium meets chloride

Abstract: A large amount of chloride and ammonium ions were produced and released from industrial processes with non-biodegradable organic pollutants to affect efficiencies of advanced oxidation processes (AOPs). Here, the influences of chloride and ammonium ions on Co/peroxymonosulfate (Co/PMS) reaction system, a widely used AOPs to produce sulfate radicals, were investigated by examining the degradation efficiency of an azo dye (Acid Orange 7, AO7). The experimental results showed that a significant decrease in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…This was probably because NH 4 + could be deprotonated to form NH 3 , which then might induce the formation of chloramines that have weak oxidation properties ( eqn (20)–(22) ). 39 Consequently, it might be concluded that Cl − , NH 4 OH, and NH 4 HCO 3 were the primary components involved in accelerating ACE degradation. NH 3 + HOCl → NH 2 Cl + H 2 O NH 2 Cl + HOCl → NHCl 2 + H 2 O NHCl 2 + HOCl → NCl 3 + H 2 O …”
Section: Resultsmentioning
confidence: 99%
“…This was probably because NH 4 + could be deprotonated to form NH 3 , which then might induce the formation of chloramines that have weak oxidation properties ( eqn (20)–(22) ). 39 Consequently, it might be concluded that Cl − , NH 4 OH, and NH 4 HCO 3 were the primary components involved in accelerating ACE degradation. NH 3 + HOCl → NH 2 Cl + H 2 O NH 2 Cl + HOCl → NHCl 2 + H 2 O NHCl 2 + HOCl → NCl 3 + H 2 O …”
Section: Resultsmentioning
confidence: 99%
“…Notably, a dual effect was found on AO7 degradation which is similar to our previous investigations. 22,37 At a low level of chloride (<1 mM), the degradation rate of AO7 declined slightly. However, further addition of chloride (>1 mM) apparently accelerated dye degradation.…”
Section: Effect Of CL à Concentrationmentioning
confidence: 99%
“…291 Moreover, positive effects of ionic strength on reaction rates were observed in various reaction systems. [292][293][294] Studies suggested that the reaction rates between oxidants and organics raised with the increase in ionic strength. 295 The ionic strength created by different ions might also inuence reaction rates.…”
Section: àmentioning
confidence: 99%